Carbonization behavior and mesophase conversion kinetics of coal tar pitch using a low temperature molten salt method - Cheng, Youliang; Fang, Changqing; Su, Jian; Yu, Ruien; Li, Tiehu (Journal of analytical and applied pyrolysis, 2014)
•AlCl3–NaCl molten salt is applied in the carbonization of CTP.•Mesophase conversion behaviors of CTPS are mainly influenced by the heating temperature and holding time.•This method lowers the apparent activation energy of isothermal mesophase conversion for CTP.•Key benefits are low heating temperature and short holding time for the completion of mesophase conversion. Mesophase pitch can be prepared from coal tar pitch (CTP) with AlCl3–NaCl molten salt mixture at low temperature via the molten salt method. The carbonized and mesophase products were characterized using polarized optical microscope, FTIR, XRD, 13C NMR and TEM. The kinetic parameters of the mesophase conversion were calculated by isothermal kinetics. These experimental results demonstrated that the molten salt catalyzed the mesophase transition and the formation temperature of CTP was lowered to 250°C. An abundance of mesophase spheres formed in the carbonized products when the CTP was treated with molten salt at 280°C for 30min (CTPS-280-30). The optical textures of these carbonized products exhibited mosaic anisotropy and the degree of order was reduced when the heating temperature and holding time were increased. It was found that the building units of CTPS-280-30 mesophase products were parallel molecular layers with a thickness of 0.6–2.5nm, and the building units of CTPS-280-120 were 1–3.5nm in thickness. Naphthene and methylene-bridge structures were found in the mesophase products. The kinetics study showed that the molten salt conversion of CTP to mesophase pitch was first-order kinetic with a low apparent activation energy (40.5kJ/mol).